HUBUNGAN ANTARA PEMBERIAN REMUNERASI TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT ISLAM SITI KHADIJAH PALEMBANG - Juairiah Juairiah; Rosyidah Umpu Malwa (Psikis : Jurnal Psikologi Islami, 2016)
This  study  determines  whether  there  is  a  relationship  between  the  remuneration  to  the  employee performance  at the  Islamic  Hospital  Siti Khadijah  Palembang.  The  hypothesis  of this  study  is  no significant  relationship  between  the  remuneration  to  the  employee  performance  in  The  Islamic Hospital Siti Khadijah Palembang. There are two variables in the study of variable remuneration X and Y performance. The method used is quantitative correlation. The sampling technique in studies using  stratified  random  sampling,  and  found  the  number  of  sampling  as  many  as  50  people. Instrument  collecting  data  in  this  study  using  a  scale  of  remuneration  and  performance  scale. Hypothesis testing using a hypothesis test analysis of SPSS version 22.0 for Windows. The results of data  analysis  based  on  the  analysis  of  the  Kearl  Person  Product  Moment  showed  that  there is  a significant correlation (r s> r table) = 0.666> 0.279 with significance level of 0.05. This indicates the higher administration remunersi the employee's performance will increase.